Keragaan Penyaluran Kredit Ketahanan Pangan dan Energi (KKP-E) di Kabupaten Jember - Sugiarto, Sugiarto (Jurnal Penelitian Pertanian Terapan, 2011)
Kredit Ketahanan Pangan dan Energi (KKP-E) is a perfecting program credit form Kredit Ketahanan Pangan (KKP) whiich done in 2007, the purpose is to help farmer in farming capital. This research showed that the bigest used of KKP-E is in sugar cane farming, then in crop and livestock. Nevertheless, the distribution of the credit is blocked by smooting time to farmer, especially for horticulture KKP-E which will block season. Beside standarad condition which fund is distribution of credit come from banking (executing). Banking has 5 C (Collateral, Caracter, Capacity, Capitan and Condition), and gentioneraly the most difficult condition is colleteral. The spead of farmer as debitur has not achieved all around and only limited to farmer in area which is organised in farmer group organization. So that, it is suggested to have socialization activity together among agency and banking ti ditribute KKP-E to farmer/farmer group. Keywords: KKP ? E credit, performance